Analisis Peranan Organisasi Karang Taruna Dalam Pemberdayaan Masyarakat Desa Di Desa Tambakrejo Kecamatan Krembung - Syaifudin Ma’arif; Wahyu Eko Pujianto (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This research analyzes the role of the Karang Taruna Organization (OKT) in empowering the community of Tambakrejo Village, Krembung District.  The research method uses a literature review to detail the context and success of social empowerment programs.  Analysis of social, economic and organizational factors, as well as community participation are integrated in the literature review.  Findings highlight the importance of understanding local traditions, gender engagement, and understanding community needs.  Economic factors and resource accessibility influence participation rates.  Responsiveness to feedback, inclusive programs, and developing community networks are strategies to increase participation.  This research provides a conceptual basis for designing effective empowerment programs at the village level involving OKT.